(untitled) (Research, Society and Development, 2021)
Although bone tissue regeneration is a well-defined process, complications inherent to the treatment of fractures are still observed, one of them being the participation of serotonin in bone formation and remodeling. This is a hormone responsible for the regulation of several physiological processes and is correlated with the etiology of depression, whose treatment is given, especially, through the use of selective serotonin reuptake inhibitors (SSRI), which are related to an increased risk of fracture and bone loss. Thus, the aim of this study was to analyze the action of Fluoxetine, Sertraline and Citalopram in the bone regeneration process. Thirty-five Wistar rats were used, in which bone defects of 2 to 3 mm in length were made in the fibula. The animals received Fluoxetine Hydrochloride 60 days before the fracture was made, and Sertraline Hydrochloride and Citalopram Hydrochloride 40 days before, and continued for another 30 days after the procedure. Control animals received saline solution. The results show that the bone defect regeneration process occurred more effectively in animals belonging to the control group, when compared to the other treated groups. The same data were observed regarding the serum alkaline phosphatase rate, statistically different when compared to animals treated with SSRIs. These data allow us to suggest that Fluoxetine, Sertraline and Citalopram seem to negatively interfere in the bone regeneration process, leading to a delay and non-complete consolidation of fractures with bone loss.